Nonlinear Incentive Provision in Walrasian Markets : A Cournot Convergence Approach - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2004)
The paper studies insurance with moral hazard in a system of contingent-claims markets. Insurance buyers are modelled as Cournot monopolists or oligopolists. The other agents condition their expectations on market prices, as in models of rational-expectations equilibrium with asymmetric information. Thereby they correctly anticipate accident probabilities corresponding to effort incentives induced by insurance buyers? net trades. When there are many agents to share the insurance buyer?s risk, Cournot equilibrium outcomes are close to being second-best. In contrast, if insurance buyers are price takers, equilibria fail to exist or are bounded away from being second-best.
Keywords: 330; Insurance; Moral Hazard; Incentive Contracting; Walrasian Markets; Rational-Expectations; Cournot Equilibrium; Versicherungsökonomik; Moral Hazard; Anreizvertrag; Monopson; Rückversicherung; Optionsgeschäft; Allgemeines Gleichgewicht; Nash-Gleichgewicht; Rationale Erwartung; Theorie